1988
DOI: 10.1111/j.1365-2133.1988.tb02591.x
|View full text |Cite
|
Sign up to set email alerts
|

Dysplastic naevus in non-familial melanoma. A clinicopathological study of 101 cases

Abstract: In 101 patients with non-familial cutaneous melanoma (CM), melanocytic naevi were counted and classified according to clinical criteria. Only 8% of the patients had very atypical naevi. These atypical naevi were few in number and only one patient exhibited dysplastic naevus syndrome. An histological study was undertaken on the hypothesis that, in a given individual, if the most clinically atypical naevus is not histologically dysplastic it is unlikely that any of the others are. The most clinically atypical na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…It is of interest that Grob et al [29) reported a prev alence of 18% histologically confirmed DMN in a series of nonfamilial melanoma patients, which is similar to the figure of 18.3% in our nonfamilial cases. Other authors have recorded somewhat higher frequencies, e.g.…”
Section: Discussionsupporting
confidence: 73%
“…It is of interest that Grob et al [29) reported a prev alence of 18% histologically confirmed DMN in a series of nonfamilial melanoma patients, which is similar to the figure of 18.3% in our nonfamilial cases. Other authors have recorded somewhat higher frequencies, e.g.…”
Section: Discussionsupporting
confidence: 73%
“…The lack of correspondence between clinically dysplastic nevi and histologically dysplastic nevi has been well documented [18,29,30]. This is not surprising, given the lack of universally accepted criteria for dysplastic nevi.…”
Section: Discussionmentioning
confidence: 88%
“…Grob JJ et al (1988) [11] showed that the diagnosis of dysplastic naevi on the basis of clinical criteria alone is difficult and unreliable. Kwok YK et al (2001) [12], in their study on melanocytic naevi, reported a lack of clinicpathological concordance in dysplastic naevi.…”
Section: Discussionmentioning
confidence: 99%